2016
DOI: 10.1016/j.jmii.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multiplex Luminex assay for detecting swine antibodies to structural and nonstructural proteins of foot-and-mouth disease virus in Taiwan

Abstract: The results indicated that xMAP has the potential to detect antibodies to FMDV-SP-VP1 and NSP-3ABC and to distinguish FMDV-infected pigs from pigs infected with the swine vesicular disease virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…The purified protein and antibodies were then shown to be specific to serotype O when tested against serotypes A, O, C and Asia-1 in an enzyme-linked immunosorbent assay (ELISA) and latex agglutination test (Suryanarayana et al 1999). The reliable differentiation of serotype-specific antibodies with recombinant VP1 was demonstrated by Wenger et al (1999) and by Chen et al (2016) in an indirect ELISA and Luminex assay respectively. Recombinant VP1 protein was also used as antigen on an immunochromatographic strip for specific rapid detection of FMDV serotype O (Yang et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…The purified protein and antibodies were then shown to be specific to serotype O when tested against serotypes A, O, C and Asia-1 in an enzyme-linked immunosorbent assay (ELISA) and latex agglutination test (Suryanarayana et al 1999). The reliable differentiation of serotype-specific antibodies with recombinant VP1 was demonstrated by Wenger et al (1999) and by Chen et al (2016) in an indirect ELISA and Luminex assay respectively. Recombinant VP1 protein was also used as antigen on an immunochromatographic strip for specific rapid detection of FMDV serotype O (Yang et al 2010).…”
Section: Introductionmentioning
confidence: 98%
“…However, less work has been carried out using this technology in the veterinary field (3238) and there are only a few commercial kits available. Moreover, when compared to conventional ELISA, previous results have shown that xMAP formats can be more sensitive and reproducible (35).…”
Section: Introductionmentioning
confidence: 99%
“…This technology combines fluorescent-dyed microspheres, a detection instrument based on lasers read-out, digital signal processing and an analysis software (Christopher-Hennings et al, 2013;Graham et al, 2019). While BBMAs are widely applied in human health, with the development of methods for drug discovery (Komnatnyy et al, 2018), diseases diagnosis (Grignard et al, 2019;Lu et al, 2005) and immune response characterisation (Jones et al, 2002) among others, work in the veterinary field has been more limited, although interest has been rising recently (Chen et al, 2016;Fabian et al, 2020;Hoste et al, 2020;Laamiri et al, 2016;Ragan et al, 2018). To date, there are a few commercial assays available (References TRD-500 and TRD-502, Biovet Inc. Saint-Hyacinthe, Canada).…”
Section: Introductionmentioning
confidence: 99%